CORRELATION BETWEEN FERRITIN, IL-6 AND IL-1Β: INFLAMMATORY AND THERAPEUTIC IMPLICATIONS IN CARDIOVASCULAR DISEASES - Flavio Gomes Jardim Filho, Marcelo (Health and Society, 2024)
Inflammation plays a central role in the pathogenesis of cardiovascular diseases (CVDs), with the pro-inflammatory cytokines IL-6 and IL-1β exerting direct influence on atherosclerosis progression, endothelial dysfunction, and adverse cardiovascular outcomes. This article reviews the correlations between ferritin, an inflammatory and metabolic biomarker, and the cytokines IL-6 and IL-1β, emphasizing their relevance in chronic inflammatory states and their association with cardiovascular dysfunction. Ferritin, often elevated in response to IL-6 and IL-1β activity, reflects both an attempt by the organism to mitigate oxidative damage and a marker of inflammatory aggravation. Recent studies, including clinical trials with anti-inflammatory agents such as canakinumab, colchicine, and tocilizumab, suggest that targeted inhibition of these inflammatory pathways can significantly improve cardiovascular outcomes. Finally, this review highlights the need for personalized therapeutic strategies, considering patients’ inflammatory profiles and biomarkers, to optimize clinical interventions and improve prognosis in CVDs.